2019
DOI: 10.1016/j.scitotenv.2019.05.416
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three Australian natural organic matter isolates to the Suwannee river standard: Reactivity, disinfection by-product yield, and removal by drinking water treatments

Abstract: Comparing three Australian natural organic matter isolates to the Suwannee river standard: reactivity, disinfection by-product yield, and removal by drinking water treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…This opposite trend can be explained in terms of the different SUVA values, high and low, for Suwannee River and Lake Kinneret, respectively. The high SUVA of Suwannee River indicates that a large fraction of the DOM is composed of dissolved humic substances as reported (Croue et al, 2000;Korshin et al, 1999;Watson et al, 2019), which have a high attraction to the positively charged GPDADMAC-MMT sorbent.…”
Section: Adsorption Of Dom From Lake Kinneret By Gac and Gpdadmac-mmt Columnsmentioning
confidence: 58%
“…This opposite trend can be explained in terms of the different SUVA values, high and low, for Suwannee River and Lake Kinneret, respectively. The high SUVA of Suwannee River indicates that a large fraction of the DOM is composed of dissolved humic substances as reported (Croue et al, 2000;Korshin et al, 1999;Watson et al, 2019), which have a high attraction to the positively charged GPDADMAC-MMT sorbent.…”
Section: Adsorption Of Dom From Lake Kinneret By Gac and Gpdadmac-mmt Columnsmentioning
confidence: 58%
“…NOM consists of carbon-containing substances and energy sources for aquatic organisms and can, thus, influence the carbon cycle and ecosystems. In addition, it is considered a problematic material that causes taste, odor, and membrane fouling and produces disinfection byproducts in drinking water [4][5][6]. Therefore, NOM has been the subject of extensive research over the past few decades in environmental science and engineering fields.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…The former contained 97% of hydrophobic fraction, whereas the latter only had 23%. In addition, Watson et al [5] reported differences in the reactivity of NOMs obtained from vari-ous sources. Three drinking water sources in Australia were studied, in which SRNOM was treated using different water purification processes to compare the removal efficiency between the NOMs from the three water sources and SRNOM.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Since the presence of THMs in drinking water is related to the increase in cases of bladder cancer, rectal cancer, and spontaneous abortion, the maximum contaminant level [MCL] of THMs were set by the environmental agencies. Nowadays, the maximum concentration of THMs is established at 100 µg L −1 both in the USA and Europe [3,4].…”
Section: Introductionmentioning
confidence: 99%